Radicalization Leading to Violence: A Test of the 3N Model - Bélanger, Jocelyn J.; Moyano, Manuel; Muhammad, Hayat; Richardson, Lindsy; Lafrenière, Marc-André K.; McCaffery, Patrick; Framand, Karyne; Nociti, Noëmie (Frontiers in Psychiatry, 2019)
The present research examines the social cognitive processes underlying ideologically-based violence through the lens of the 3N model of radicalization. To test this theory, we introduce two new psychometric instruments —a social alienation and a support for political violence scale— developed in collaboration with twelve subject matter experts on terrorism. Using these instruments, we test the theory’s postulates in four different cultural settings. In Study 1, Canadians reporting high levels of social alienation (Need) expressed greater support for political violence (Narrative), which in turn positively predicted wanting to join a radical group (Network), controlling for other measures related to political violence. Study 2a and 2b replicated these findings in Pakistan and in Spain, respectively. Using an experimental manipulation of social alienation, Study 3 extended these findings with an American sample and demonstrated that moral justification is one of the psychological mechanisms linking social alienation to supporting political violence. Implications and future directions for the psychology of terrorism are discussed.